Pengaruh Edukasi Terhadap Pengetahuan dan Konsumsi Junk Food Pada Pasien Hipertensi di Puskesmas Klungkung I - Cahyaningsih, I Gusti Ayu Diah; Juniarsana, I Wayan; Suiraoka, I Putu (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
The development of the times tends to make people adopt a modern lifestyle. People prefers instant things such as consumption junk food. Consumption habits of  junk food is one of the causes of hypertension. Increasing knowledge about the various causes of hypertension can reduce hypertension sufferers. This research aims to determine the effect of education on knowledge and consumption junk food in hypertensive patients at Klungkung I Community Health Center. Type of research is as if experimental with research design one grup pre test- post test design. The research was carried out from December 2023 to January 2024. The research sample was 42 people taken using the technique purposive sampling. Data collection was carried out by interviews using questionnaires and blood pressure measurements. The results of the research show that there is an increase in knowledge before and after education is carried out, so there is an effect of providing education on knowledge (p 0.05), there are changes in consumption patterns in type and frequency junk food namely before and after education is provided, there is an influence of education on type junk food  and frequency junk food consumed (p 0,05).Keywords: Knowledge, Junk food consumption, Education